Experiencia de panamá en el tratamiento laboral, del coronavirus (covid-19) - Núñez Morales, Rórix Javier (2026)
In this essay, we identify the main labor guidelines adopted in the Republic of Panama since the State of National Emergency for Covid-19 was declared last March. This health crisis that has demanded, as a priority, safeguarding the life and health of the entire population, and with respect to preventive measures, exceptional restriction of labor and social activities, the ad-hoc labor regulations have sought to revalidate the preeminence of health by imposing limits on operations in workplaces, promoting teleworking and establishing other temporary measures. The figures of lost jobs and the effects on small and large companies as a result of the coronavirus, are dramatic. Therefore, we allow ourselves to ensure that everything leads to the pressing need to settle spaces for dialogue and agreement among actors involved and affected in this great crisis. Therefore, we propose some priorities for timely, perhaps premature, reflections though the urgency of the moment prompts us to do so.